Difficult Preoperative Diagnosis of Suspected Metal Hypersensitivity in a Case with Early Failure of Bipolar Hemiarthroplasty - Airi Shimmyo; Yu Takeda; Shigeo Fukunishi (Case Reports in Orthopedics)
Background. Metal hypersensitivity is a rare complication after total hip arthroplasty (THA), and no reliable diagnostic method for metal hypersensitivity to orthopedic metal implants has yet been established. Case report. A 57-year-old woman underwent hemiarthroplasty using a metal implant despite a skin allergy to metal jewelry. Two years after surgery, the patient developed early hemiarthroplasty failure and refractory erythema. Although the patient was clinically suspected to have a hypersensitivity to metal, the preoperative screening test was negative, and patient underwent revision surgery with cemented THA. Postoperatively, the erythema as well as her hip pain disappeared completely. Conclusion. Patients with clinically suspected metal hypersensitivity should undergo primary and revision total hip arthroplasty using hypoallergenic implants regardless of preoperative screening results.